BIMBINGAN TEKNIS IMPLEMENTASI MODEL JOYFULL LEARNING BAGI GURU IPS SMP DI KOTA SEMARANG (Universitas Negeri Semarang, 2019)
Social studies subjects are one of the subjects that are closely related to the community environment in the learning process. Joyful Learning will lead to student learning motivation. Unfortunately social studies teachers are still limited in applying models in the classroom. So it is necessary to implement Technical Guidance for the Implementation of Joyful Learning Models for Social Studies Teachers of Junior High Schools in Semarang City. The objectives of the Community service activities are (1) Collaborating jointly with partners regarding what learning models have been used by the teachers in Semarang City Junior High School; (2) Studying jointly with partners related to the implementation of social studies learning which has been carried out in Semarang City Junior High School; (3) Providing technical guidance for implementing Joyful Learning models for Social Studies teachers in Semarang City Junior High School. The method of implementing community service activities uses two approaches namely textual and contextual. The procedure in this community service activity includes: (1) Exploratory; (2) Topical; (3) Monitoring and Evaluation. The results of the implementation of this community service activity can be seen that the learning model used by teachers in Semarang City Junior High School is still teacher centered and the learning model is still based on indoor learning. Guidance The implementation technique of the joyful learning model gets the result that the learning objectives must contain elements of ABCD (Audience, Behavior, Condition, and Degree), regular material and remidial material levels may be the same, but for enrichment materials must be higher, assessment of knowledge must have stimulus on the test, indicators of competency achievement to be achieved must also be integrated Mata pelajaran IPS merupakan salah satu mata pelajaran yang erat kaitannya dengan lingkungan masyarakat dalam proses pembelajarannya. Pembelajaran yang dirancang secara menyenangkan (Joyfull Learning) akan menimbulkan motivasi belajar peserta didik. Sayangnya guru IPS masih terbatas dalam mengaplikasikan model di kelas. Sehingga perlu dilaksanakan Bimbingan Teknis Implementasi Model Joyfull Learning bagi Guru IPS SMP di Kota Semarang. Tujuan daripada kegiatan PPM ini adalah (1) Mengkaji secara bersama dengan mitra terkait dengan apa saja model pembelajaran yang selama ini digunakan oleh guru-guru di SMP Kota Semarang; (2) Mengkaji secara bersama dengan mitra terkait dengan pelaksanaan pembelajaran IPS yang selama ini telah dilaksanakan di SMP Kota Semarang; (3) Memberikan bimbingan teknis implementasi model Joyfull Learning bagi guru IPS SMP di Kota Semarang. Metode pelaksanaan kegiatan pengabdian menggunakan dua pendekatan yaitu tekstual dan kontekstual. Prosedur dalam kegiatan pengabdian kepada masyarakat ini meliputi: (1) Exploratory; (2) Topical; (3) Monitoring and Evaluation. Hasil pelaksanaan kegiatan pengabdian ini dapat diketahui bahwa model pembelajaran yang digunakan oleh guru di SMP Kota Semarang masih terpusat pada guru (teacher oriented) serta model pembelajaran yang masih berbasis indoor learning. Bimbingan Teknik implementasi model pembelajaran joyfull learning mendapatkan hasil bahwa tujuan pembelajaran harus memuat unsur ABCD (Audience, Behavior, Condition, dan Degree), materi reguler dan materi remidial tingkatannya boleh sama, namun untuk materi pengayaan harus lebih tinggi, penilaian pengetahuan harus ada stimulus dalam soalnya, indikator pencapaian kompetensi yang ingin dicapai juga harus terpadu.